Pencegahan Bencana Tanah Longsor Berbasis Pemberdayaan Masyarakat dengan Sistem Informasi Geografi di Desa Sirau, Kecamatan Karangmoncol Kabupaten Purbalingga, Jawa Tengah: Landslide Disaster Prevention Based on Community Empowerment using a Geographic Information System in Sirau Village, Karangmoncol District, Purbalingga Regency, Central Java - Candra, Adi; Siswandi, Siswandi; Permanajati, Indra (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Efforts to minimize the impact of landslides could be conducted by figuring out the mechanism of landslides so that mitigation could be prevented. Focusing on detailed mapping which potentially causes landslides should be increased continuously and entered into a database that is used for information on village profiles where it is usefully built up in the future. Mapping of landslides involved communities participating who are represented by the Community of Disaster Response (MASTANA) that needed to be developed in villages with huge landslides potentially. Landslide mapping is most important due to the source of maps that had been issued by the Center for Volcanology and Geological Disaster Mitigation (PVMBG) ESDM has a small scale to reach village territory. The result shows that only MASTANA members prepared when a landslide occurred when it could be predicted based on a visual observation. Initial detection of landslides potential and notes on Geographic Information System are used to an information about landslides spread out.